2016
DOI: 10.1016/j.vhri.2016.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Estimación de la Relación Costo-Efectividad de las Vacunas Neumocócicas Conjugadas Prevenar-13 y Synflorix®, Utilizadas en Los Programas de Vacunación de Población Infantil Mexicana

Abstract: Even though the simulations for Prevenar-13 and Synflorix® revealed both of them to be cost-effective when used to instrument pediatric vaccination campaigns in Mexico, Synflorix® had a better cost-utility/effectiveness profile. In addition, although Prevenar-13 and Synflorix® produced equivalent health outcomes, the overall analysis predicted that Synflorix® would save 360 million Mexican pesos, as compared with Prevenar-13.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…A more recent analysis by Gomez and colleagues (2016) determined that PCV10 would be the cost-saving option compared to PCV13. 9 The results from this study however were driven entirely by the benefits of PCV10 preventing OM caused by non-typable Haemophillus influenza (NTHi) based on evidence from an investigational PCV11 vaccine. However, recent studies have shown PCV10 did not demonstrate any statistically significant effect on NTHi-clinically confirmed These scenarios assume that serotype replacement may take several years to occur given sustained use of PCV13 in years before switch.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…A more recent analysis by Gomez and colleagues (2016) determined that PCV10 would be the cost-saving option compared to PCV13. 9 The results from this study however were driven entirely by the benefits of PCV10 preventing OM caused by non-typable Haemophillus influenza (NTHi) based on evidence from an investigational PCV11 vaccine. However, recent studies have shown PCV10 did not demonstrate any statistically significant effect on NTHi-clinically confirmed These scenarios assume that serotype replacement may take several years to occur given sustained use of PCV13 in years before switch.…”
Section: Discussionmentioning
confidence: 92%
“…Previous economic evaluations of PCVs in Mexico have a number of important limitations that this analysis improves upon. 8,9 An early study by Mucino-Ortega and colleagues (2010) determined PCV13 was cost-saving compared to PCV10. However this analysis did not consider the impact of herd effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By modeling each serotype individually by age group at a population level, this analysis more accurately estimates potential serotype replacement in the event of a vaccine switch. This methodology also provides a more realistic picture of how the vaccination programs may behave as it relies on real-world effectiveness data as opposed to the efficacy data used in most existing analyses [ 8 , 11 , 47 51 ]. This means that the forecasts inherently capture vaccine dynamics observed in the real world, such as vaccine waning, cross-reactivity, and herd protection.…”
Section: Discussionmentioning
confidence: 99%
“…An investigational 11-valent vaccine in which all serotypes were conjugated to protein D, a highly conserved protein from NTHi, showed statistically significant efficacy against all AOM episodes due to NTHi [ 60 , 61 ]. Previous economic analyses have assumed an additional benefit for PCV10 in preventing NTHi AOM based on evidence for this investigational 11-valent vaccine [ 47 , 50 , 51 , 62 , 63 ]. However, real-world effectiveness data published over the last few years have presented mixed evidence.…”
Section: Discussionmentioning
confidence: 99%